Justice in Funding Adaptation under the International Climate Change Regime - Grasso, Marco; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Covering the ethical dimensions of international-level adaptation funding, a subject of growing interest in the climate change debate, this book provides a theoretical analysis of the ethical foundations of the UNFCCC regime on adaptation funding, one that culminates in the definition of a framework of justice. The text features an interpretative analysis of the ethical contents of the UNFCCC funding architecture by applying the framework of justice proposed to different areas of empirical investigation. The book offers scholars working on climate change, international relations, and environmental politics an analysis characterized by both theoretical soundness and empirical richness. The comprehensiveness of the book$1 (Bs approach should make it possible to plan and implement international adaptation funding more effectively, and eventually to define more just funding policies and practices.s
Adaptation to Climate Change -- The Ethical Bases of International Adaptation Funding -- The Framework of Justice -- The International Institutions and Instruments Governing Adaptation Funding -- Evaluation of Procedural Justice in International Adaptation Funding -- Evaluation of Distributive Justice, Analysis of Fairness and Equity Criteria and of the Role of Justice in International Adaptation Funding -- Further Application of the Framework of Justice and Concluding Remarks.
Keywords: Environmental sciences; Ethics; Political science -- Philosophy; Geography; Climatic changes; Environmental economics; Political science; Environment; Climate Change; Political Philosophy; Political Science; Geography (general).; Ethics; Environmental Economics